Belimumab use during pregnancy: Interim results of the belimumab pregnancy registry. Issue 2 (30th September 2022) - Juliao, Patricia; Wurst, Keele; Pimenta, Jeanne M.; Gemzoe, Kim; Landy, Helain; Moody, M. Anthony; Tilson, Hugh; Covington, Deborah; Moore, Tammy; Marino, Rebecca; Gilbride, Jennifer; Liu, Andrew; et al.
Abstract: Background: Belimumab is approved for active, autoantibody‐positive systemic lupus erythematosus (SLE) and lupus nephritis, but limited data exist regarding its use in pregnancy. The Belimumab Pregnancy Registry (BPR, GSK Study BEL114256; NCT01532310) was created to evaluate pregnancy and infant outcomes following belimumab exposure. Methods: Individuals with SLE exposed to belimumab from 4 months before and/or during pregnancy can enroll into the BPR. The primary outcome is major birth defects; secondary outcomes include miscarriages, stillbirths, elective termination, pre‐term birth, neonatal death, small for gestational age, and adverse infant outcomes during the first year of life. Belimumab exposure timing, concomitant medications, and other potential confounding factors are also collected. Data up to March 8, 2021, are reported descriptively. Results: From an expected sample size target of 500 prospective pregnancies with a known outcome, only 55 were enrolled in the study. Among these, two pregnancy losses and 53 pregnancies with a live birth outcome were reported. Ten of the 53 live birth pregnancies resulted in a major birth defect. Ten pregnancies were enrolled after the pregnancy outcome occurred and were examined retrospectively (four live births with no defects, four miscarriages, and two elective terminations). There was no indication or pattern of birth defects associated with belimumab. Conclusions: Low recruitment numbers for the BPR and incomplete information limit the conclusions regarding belimumab exposure during pregnancy. There was no pattern or common mechanism of birth defects associated with belimumab within the BPR data.